Comparison of plasma malondialdehyde, glutathione, glutathione peroxidase, hydroxyproline and selenium levels in patients with vitiligo and healthy controls - Ozturk I; Batcioglu Kadir; Karatas Fikret; Hazneci Ersoy; Genc Metin (Wolters Kluwer Medknow Publications, 2008)
Background: The etiology and pathophysiologic mechanism of vitiligo are still unclear. The relationship between increased oxidative stress due to the accumulation of radicals and reactive oxygen species and the associated changes in blood and epidermal component of vitiliginous skin have been reported many times. We investigated the possible changes of plasma malondialdehyde, glutathione, selenium, hydroxyproline and glutathione peroxidase activity levels in patients with vitiligo in order to evaluate the relationship between oxidative stress and etiopathogenesis of vitiligo. Materials and Methods: Plasma malondialdehyde, glutathione, hydroxyproline and glutathione peroxidase activity levels were measured by spectrophotometric methods, and HPLC was used for measurement of selenium concentrations. Results: Our results showed increased malondialdehyde, hydroxyproline and glutathione peroxidase activity levels in plasma of vitiligo group ( P < 0.05). Conclusion: Support of antioxidant system via nonenzymatic antioxidant compounds and antioxidant enzymes may be useful to prevent of melanocyte degeneration which occur due to oxidative damage in vitiligo.